Enhancing Creative Thinking Through Project Based Learning: Study of Fourth-Grade Elementary Students - Khairiyah, Ummu; Dia Ayu Pramudita; Muchammad Bayu Tejo Sampurno (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Creative thinking skills are an essential 21st-century competency that needs to be developed from the elementary school level. This study aims to analyze the effect of implementing the Project Based Learning (PjBL) model on the creative thinking skills of fourth-grade elementary school students. The research employed a quantitative method with a one-group pre-test-post-test design. The participants consisted of 25 students from one elementary school in Lamongan. The instrument used was an essay test to measure creative thinking skills, which had met the validity and reliability tests. The results of the Shapiro-Wilk normality test indicated that the data were normally distributed (pre-test = 0.061; post-test = 0.189). Data analysis using a Paired Sample t-test in SPSS version 25 yielded a significance value of 0.000 (p < 0.05), indicating that H₀ was rejected and Hₐ was accepted. This finding proves a significant effect of the PjBL model on improving students' creative thinking skills, as reflected in the increase in the average score from 43.4 (pre-test) to 80.24 (post-test). These results imply that PjBL can be relied upon as an effective learning model to foster students' creative thinking skills in science learning contexts, particularly on the topic of energy transformation.